POESIA ARABA E SUFISMO NELL’ETIOPIA CONTEMPORANEA,FRA PRATICA E DOTTRINA - Petrone, Michel (El Azufre Rojo, 2021)
Riassunto: In questo studio si prenderanno in esame alcuni esempi provenienti dall’Etiopia Sud Occidentale, tutt’ora inediti. Composti da Sufi locali fra la fine del XIX secolo e l’inizio del XX, questi testi mostrano un profondo legame con la pratica del mawlid come festività popolare. Allo stesso tempo i versi racchiudono alcuni insegnamenti metafisici di scuola akbariana. Abstract: Sufi poetry is widespread, in Arabic and local languages, throughout the Islamic world. In this study, some examples from Southwestern Ethiopia, still unpublished, will be examined. Composed by local Sufis between the end of the nineteenth century and the be-ginning of the twentieth, these texts show a profound link with the practice of the mawlid as a popular festival. At the same time the verses contain some metaphysical teachings of the Akbarian school.